Association between hormonal therapy and craniofacial development in subjects between 10 and 18 years of age. Systematic review - Ceballos, Juliana Isabel; Pineda, Sebastián; Rueda, Zulma Vanesa; Lema, María Clara; Johnson, Natalia (Revista Estomatología, 2014)
Background: Hormone deficiency could affect craniofacial complex during esqueletal growth and development.Objective: Determine whether there is scientific evidence of the association between hormonal treatment and craniofacial growth measured by cephalometry films, in subjects of 10 to 18 years with hormonaltreatment.Materials and Methods: A systematic review. For the articles published in PubMed, Google Scholar, Lilacs, Embase and Science Direct databases, without restriction of publication year was performed. Clinicaltrials, case control studies, cohort, systematic reviews and meta analysis studies were included. Reading f the abstracts and the complete articles were made by two researchers.Results: Among 1085 articles found, 1074 were excluded because did not meet the inclusion criteria. After complete reading of the articles, five were excluded because they were cross-sectional studies and one was not recovered in the full text. In total, 6 articles were included. These studies report that patients who were treated with hormone substitution therapy showed favorable changes in their craniofacial structures, especially in mandibular total length, ramus length and mandibular body length. These positive changes led to an improvement in profile, inter-maxillary relations, and other osseous body structures.Conclusions: Despite the heterogeneity of the studies it was found that early replacement with hormone treatment, regardless of the dose and long-term treatment, accelerates the development of craniofacial structures, mainly the mandible, to reach the skeletal patterns genetically established. Studies are required to evaluate replacehormone treatment in patients without additional systemic compromises.